Responding to Gender-Based Rejection: Objecting Against Negative and Disproving Positive Intergroup Differentiation. (March 2013) - Cihangir, Sezgin; Scheepers, Daan; Barreto, Manuela; Ellemers, Naomi
We examined whether women ( N = 87) who are exposed to blatant discrimination show different responses depending on whether they are rejected with reference to positively ("this is something for men") or negatively ("this is nothing for women") phrased intergroup differentiation. Based on current insights on responses to discrimination, we predicted and found that those who are exposed to negative differentiation will tend to object to those who rejected them, while positive differentiation is more likely to induce efforts to disprove the validity of the rejection. Female participants facing negative differentiation objected against the discriminatory nature of their rejection and showed cardiovascular reactivity more indicative of threat (and less of challenge) than participants in the positive differentiation condition. In addition, positive differentiation caused participants to disprove the validity of these group-based expectations by claiming the possession of relatively more masculine (and less feminine) traits.